Perancangan Bisnis Jasa Persewaan Dekorasi Rovecè Decoration Untuk Menerapkan Inovasi Loase/Loan Untuk Target Market Usia 21-27 Tahun di Surabaya - Grace Natalian; Pramesti Saniscara (Universitas Ciputra Surabaya, 2017)
The title of this journal is Designing a Service Business of Rental Decoration for Rovecè Decoration to apply the innovation of Loase / Loan for target audiences aged 21-27 years in Surabaya. Table decoration is equivalent to any celebration, from birthday parties, bridal showers, anniversaries, to special occasions such as Christmas, Chinese New Year, etc. This research aims to perform the innovation of loase / loan, a table decoration equipment rental company, so that consumers can create their own decoration as they desire. By providing an opportunity for Surabaya residents who want to create an event, but do not have the equipments to decorate. This decoration equipment rental service business can enhance the customers satisfaction for Rovecè company. Methods that are used for this study includes qualitvative method which is done by interviewing the expert user of the owner of table decoration printing agency in Surabaya and the owner of table decoration in Surabaya and some customers of table decoration in Surabaya. Also, quantitave method which spreads quetionnaires to target audiences to determine the feasibility of this business. Preliminary result shows that 67 out of 100 people have used decoration services due to their good designs. While 33 out of 100 people said that they have never used decoration service because there hasn’t been any event that requires decorating service, but they are interested in using the services of the table decorations. Based on this, we can conclude that their rental decorations can add to the consumer interest will be decorating services, but it also can answer the problems of people who want to decorate their own events.